2016
DOI: 10.1136/bjsports-2016-096584
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well-being and training load predict in-season injury and illness risk in female youth soccer players

Abstract: Lower mood and higher acute TL are associated with increased injury risk, while higher chronic TL increases the risk of illness. Monitoring well-being and TL may facilitate intervention to reduce in-season injury and illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(152 citation statements)
references
References 46 publications
6
139
0
2
Order By: Relevance
“…Well-being predicted injury risk and injury severity This study confirms the findings of previous research demonstrated an association between well-being and injury risk (Lavallée and Flint, 1996;Watson, Brickson, Brooks, and Dunn, 2017). In specifically, both negative life-event stress (Ivarsson, Johnson, and Podlog, 2013;Johnson and Ivarsson, 2011) or daily hassles (Laux, Krumm, Diers, and Flor, 2015;Lavallée and Flint, 1996;Petrie, 1993), likely associated with subjective well-being, have been found to influence injury risk.…”
Section: Reduction In Well-being the Current Week Of Injurysupporting
confidence: 88%
“…Well-being predicted injury risk and injury severity This study confirms the findings of previous research demonstrated an association between well-being and injury risk (Lavallée and Flint, 1996;Watson, Brickson, Brooks, and Dunn, 2017). In specifically, both negative life-event stress (Ivarsson, Johnson, and Podlog, 2013;Johnson and Ivarsson, 2011) or daily hassles (Laux, Krumm, Diers, and Flor, 2015;Lavallée and Flint, 1996;Petrie, 1993), likely associated with subjective well-being, have been found to influence injury risk.…”
Section: Reduction In Well-being the Current Week Of Injurysupporting
confidence: 88%
“…Overtraining, stress, and inadequate rest may individually or jointly contribute to risk of injuries among athletes in soccer and other youth sports. 58,87,88 As previously mentioned, an acute increase in training load has been shown to be an independent risk factor for injury in youth soccer players. Current evidence is insufficient to support the uniform use of headgear or mouth guards to prevent concussion.…”
Section: Neuromuscular and Biomechanical Trainingmentioning
confidence: 82%
“…49,54,55 Although this has not been studied in youth soccer specifically, history of previous concussion may also increase the risk of subsequent lower-limb injury among collegiate athletes and represents an important area of future investigation. 56,57 Sport participation history and training loads may also influence the risk of injury in youth athletes, [58][59][60] but further information is needed to guide recommendations for soccer players specifically. Injury risk does seem to increase with age, but the relationship with competition level is unclear.…”
Section: Injury Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional soccer is characterized by high training loads, weekly competition, and frequent periods of congested fixtures (Nedelec et al, 2012;Lundberg & Weckström, 2017;Thorpe et al, 2017). High physical demands can leave players more susceptible to overtraining (Brink, Visscher, Coutts, & Lemmink, 2012), illnesses (Brink, Nederhof, Visscher, Schmikli, & Lemmink, 2010), injuries (Watson, Brickson, Brooks, & Dunn, 2016), and psychosocial disorders (Gouttebarge, Backx, Aoki, & Kerkhoffs, 2015), all of which might negatively affect both acute and longer-term performance (Brink et al, 2012;Nedelec et al, 2012;Thorpe et al, 2015). To minimise the potential deleterious effects of such high physical demands, and to assess a players performance readiness, individual training loads are closely monitored by utilising objective and/or subjective measurement tools (Saw, Main, & Gastin, 2016;Thorpe et al, 2015Thorpe et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%